Comparing Betadine and Clotrimazole for Otomycosis Treatment: A Study of Clinical Efficacy and Recurrence Rates - Mehmood Ullah, Naveed Ahmed, Muhammad Iqbal, Ikram Ullah, Jamshed Khan, Wajih Ud Din Shinwari, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Otomycosis is a common fungal infection of the external auditory canal, often causing significant discomfort and complications. Various treatments are available, with Betadine (povidone-iodine) and Clotrimazole being commonly used. This study aims to compare the efficacy of these two treatments in 130 patients. Methods: A randomized controlled trial was conducted with 130 patients diagnosed with otomycosis. Patients were assigned to receive either Betadine (10% povidone-iodine) or Clotrimazole (1%) ear drops for 14 days. Clinical assessments, including symptom resolution, fungal culture results, and recurrence rates, were recorded at days 10 and 21 post-treatment. Results: Both treatments demonstrated significant symptom relief and fungal clearance. By day 21, 87.7% of the Betadine group and 85.4% of the Clotrimazole group showed symptom resolution. The fungal culture was negative in 90.8% and 88.5% of patients, respectively. Recurrence rates at 21 days were comparable (12.3% for Betadine, 14.6% for Clotrimazole). Conclusion: Both Betadine and Clotrimazole are effective for the treatment of otomycosis, with no significant difference in outcomes. This provides clinicians with two reliable treatment options for managing otomycosis. Keywords: Otomycosis, Betadine, Clotrimazole, Antifungal Therapy, Povidone-Iodine, External Auditory Canal Infection